A Vida Sexual (1901-1933) de Egas Moniz: um discurso médico-científico sobre os corpos sexuados - Eliza Teixeira de Toledo (2015)
The purpose of this dissertation is to analyze the construction of notions of normal and pathological sexuality proposed by the Portuguese neurologist Egas Moniz (1874-1955) in two volumes of the book A Vida Sexual (1901-1933). The book is constructed by the intersection of different discourses from several knowledge fields, such as psychiatry and psychoanalysis. We propose a historical analysis of the context of production of the book and its medical contents from a gender point of view. Our attempt is to discuss, therefore, the production of a medical knowledge that determines the pattern of healthy and pathological sexuality which is grounded in a model of sexual differentiation developed in the Western, with contribution of medical discourses produced since the eighteenth century. By categorizing what was considered a deviant sexuality and, accordingly, its clinical control, Moniz,similar to a wide bibliography from this context, also sought to regulate women social behavior, in order to respond to contemporary challenges on the existing gender roles.